Beyond the border: comparative ethnobotany in Valmalenco (SO, Italy) and Valposchiavo (Canton of Grisons, Switzerland) - Fabrizia Milani; Martina Bottoni; Lorenzo Colombo; Paola Sira Colombo; Piero Bruschi; Claudia Giuliani; Gelsomina Fico (BMC, 2024)
Abstract Background The ethnobotanical analysis of two bordering areas allows for the in-depth understanding of the dynamics of Local Ecological Knowledge, which mirrors the naturalistic, historical, and sociopolitical features of each area. As part of the Interreg Italy-Switzerland B-ICE&Heritage and GEMME projects, this work is an ethnobotanical comparative study of two neighboring Alpine territories: Valmalenco (Italy) and Valposchiavo (Switzerland). Methods A total of 471 informants were interviewed on different fields of use (medicinal, food, veterinary, etc.). All data were organized in Excel™ spreadsheets. Informant Consensus Factor was calculated for the pathologies reported. Jaccard's similarity indices were calculated to compare the Valmalenco and Valposchiavo areas. Subsequently, another comparison between Valmalenco/Valposchiavo and Italian/Swiss Alpine neighboring areas was carried out. Results The number of taxa for Valmalenco was 227 (77 families) and 226 in Valposchiavo (65). Out of the 10 most cited species, 7 were mentioned in both. Arnica montana L. was the most cited in Valmalenco, and Sambucus nigra L. in Valposchiavo. The 5 most cited families were the same. Regarding the medicinal and food fields, the similarity indices were fairly low (0.31 and 0.34 for the species; 0.22 and 0.31 for the uses). Concerning the comparison with Italian and Swiss Alps, similarity values were slightly higher with Italy (Valmalenco food species: 0.38 with Italy and 0.26 with Switzerland, medicinal: 0.26 IT and 0.14 SW; Valposchiavo food species: 0.36 with IT and 0.26 with SW, medicinal: 0.21 IT and 0.14 SW). Conclusion Although Valmalenco and Valposchiavo partly share natural environment, language, history, and culture, they had low similarity indices. They both seemed to have more similarities with Italy than Switzerland, maintaining low values with the surrounding territories too. They showed a common core of Local Ecological Knowledge with several divergent branches possibly due to pivotal historical happenings, as well as more modern external influences.